2013
DOI: 10.1371/journal.pone.0066748
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Injection of Human Dental Pulp Stem Cells Improves Hypoxic-Ischemic Brain Damage in Neonatal Rats

Abstract: ObjectiveTo investigate the effect of intraventricular injection of human dental pulp stem cells (DPSCs) on hypoxic-ischemic brain damage (HIBD) in neonatal rats.MethodsThirty-six neonatal rats (postnatal day 7) were assigned to control, HIBD, or HIBD+DPSC groups (n = 12 each group). For induction of HIBD, rats underwent left carotid artery ligation and were exposed to 8% to 10% oxygen for 2 h. Hoechst 33324-labeled human DPSCs were injected into the left lateral ventricle 3 days after HIBD. Behavioral assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The fact that the majority of DPSC‐derived cells were rapidly cleared despite the improvement in function corroborates the theory that DPSC promote functional regeneration of endogenous CNS tissue. In another report, DPSC transplanted into the ventricles of animals with hypoxic‐ischaemic brain damage promoted the survival and formation of neuronal and glial cells while improving functional performance as assessed by a variety of behavioural tests . Although these results implied that that DPSC may have formed new cells to replace the damaged neurons, considering the low survival rate of the grafted cells, it is plausible to assume that the achieved neuroprotection was due to indirect endogenous stimulation and protection of host neurons and glia .…”
Section: Dpsc For Repair Of Brain Injury: Potential Treatment For Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the majority of DPSC‐derived cells were rapidly cleared despite the improvement in function corroborates the theory that DPSC promote functional regeneration of endogenous CNS tissue. In another report, DPSC transplanted into the ventricles of animals with hypoxic‐ischaemic brain damage promoted the survival and formation of neuronal and glial cells while improving functional performance as assessed by a variety of behavioural tests . Although these results implied that that DPSC may have formed new cells to replace the damaged neurons, considering the low survival rate of the grafted cells, it is plausible to assume that the achieved neuroprotection was due to indirect endogenous stimulation and protection of host neurons and glia .…”
Section: Dpsc For Repair Of Brain Injury: Potential Treatment For Tbimentioning
confidence: 99%
“…In another report, DPSC transplanted into the ventricles of animals with hypoxic‐ischaemic brain damage promoted the survival and formation of neuronal and glial cells while improving functional performance as assessed by a variety of behavioural tests . Although these results implied that that DPSC may have formed new cells to replace the damaged neurons, considering the low survival rate of the grafted cells, it is plausible to assume that the achieved neuroprotection was due to indirect endogenous stimulation and protection of host neurons and glia . Using SHED cells in a model of hypoxic‐ischaemic injury of the brain in mice, it was found that SHED transplantation improved neurological function as measured by behavioural foot‐fault testing whilst preventing tissue atrophy and reducing the number of endogenous apoptotic cells .…”
Section: Dpsc For Repair Of Brain Injury: Potential Treatment For Tbimentioning
confidence: 99%
“…Recently, some scholars study that human DPSCs are transplanted into neonatal HIE animal model, the result show that human DPSCs may reduce the brain injury of mice HIE, inhibition of proinflammatory cytokines and cell apoptosis [42]; Also find that DPSCs may an directly differentiate into neurons or glial cells, promote the proliferation of host stem cell and differentiation into neurons or glial cells, meanwhile, human DPSCs also may improve the neural behavior of animal [43]. DPSCs as a new member of stem cells, it will play an key role for nerve injury disease.…”
Section: Dental Pulp Stem Cells-derived Stem Cells (Dpscs)mentioning
confidence: 99%
“…DSCs have gained great interest during the last decade because of their accessibility, (trans)differentiation potential and high proliferative capacity. Elaborate preclinical research has highlighted the underlying biological and cellular properties of different DSCs, as well as their potential application in the treatment of medical conditions [92][93][94][95][96][97], such as myocardial infarction [98], ischemic disease [99], nerve injury and other neurodegenerative disorders [70,47,[100][101][102][103][104][105]50], inflammatory diseases [106,107], diabetes [108][109][110][111][112], muscular dystrophy [113,26,114], bone/cartilage defects [115][116][117][118][119], hair follicle loss [120], skin injuries [121], salivary gland defects [122], corneal epithelial defects [123][124][125][126], and the regeneration of dental tissues [127][128][129][130]…”
Section: Applications In Regenerative Medicinementioning
confidence: 99%